Insulin and insulin-like growth factor II permit nerve growth factor binding and the neurite formation response in cultured human neuroblastoma cells. - Recio-Pinto, E (1984)
In serum-free medium, SH-SY5Y human neuroblastoma cells specifically and reversibly lost the capacity to bind 125I-labeled nerve growth factor (NGF) to the high-affinity sites (slow sites) and to respond by neurite outgrowth, unless physiological concentrations of insulin or insulin-like growth factor II were present. In serum-containing medium, anti-insulin antiserum decreased the neurite formation response to NGF, and insulin supplementation increased the number of available NGF slow sites. The low-affinity NGF fast sites are absent from SH-SY5Y cells and did not emerge on treatment with insulin. Insulin potentiated the induction of neurites by NGF in rat pheochromocytoma PC12 cells also. These results implicate a wider role for insulin and its homologs in the nervous system.